UNLOCKING THE POTENTIALS OF CHATGPT: THE EFFICACY OF CHATGPT IN ESL LEARNING OUTCOMES - Ajab Ali Lashari; Iram Munawar; Marvi Mastoi; Paras Niaz; Saeeda Anjum Buriro; Mehboob Ali Golo (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2023)
ChatGPT, a considerable language model chatbot released in late November 2022, has drawn much interest. However, there are still unanswered questions about its capabilities. With ChatGPT, an AI-driven conversational agent integrated into English Language Learning (ELL) programs, this empirical study report seeks to examine the practical outcomes. It is crucial to evaluate the practical efficiency of AI technologies in enhancing ELL outcomes as they develop. This study has been conducted to evaluate ChatGPT’s effects on ELL students’ English language competence, learner engagement, and learning outcomes. This study employed a quantitative research method to examine how ChatGPT affected students’ learning outcomes in ESL classes at Sindh Madressatul Islam University in Karachi. N=205 students from undergraduate programs were taken in survey research. The quantitative survey correlational design has been used for the data collection and analysis. It has been found that there is a significant impact of ChatGPT in ESL classes. ChatGPT helps to learn more about ESL course content, assignments, activity-based tasks and better results. AI-assisted language learning instruction helps to get respect and identity in the classroom. It is recommended that teachers should use ChatGPT in classes for learners to better-outcome-based learning. Teachers should be trained to use AI-assisted learning models and activities with the help of workshops and seminars for better future technology-based learning.